The Palgrave handbook of managing continuous business transformation - Ellermann, Horst (Springer Science and Business Media : Palgrave Macmillan, 2016)
This handbook provides a comprehensive and unparalleled reference point for studying continuous business transformation. Asserting that change will be the new normal and highlighting the fact that business transformation can never be complete, this important resource is a tool for coping with ongoing change in order to become and stay resilient, the predominant concern of executives across industries. Containing case study material to illustrate issues and solutions, The Palgrave Handbook of Managing Continuous Business Transformation takes an interdisciplinary approach weaving together strategic concepts with real-life experiences, connecting human resource issues with shifts in information technology and linking customers with the businesses from which they buy. Structured into four parts; transformational shifts, achieving customer centricity, dealing with new technology and leading the change, this handbook is crucial reading for academics, scholars and practitioners of business transformation.